Efektivitas Dari Tanaman Zodia (Evodia Suaveolens) Sebagai Insektisida Nabati Nyamuk Aedes aegypti Penyebab Demam Berdarah - Anniza Agustina; Betta Kurniawan; M. Yusran (Medula, 2019)
Dengue Hemorrhagic Fever (DHF) is a problem of one infectious disease in the community. Dengue virus infection through Aedes aegypti mosquito bites to humans as a vector. Eradication of vectors using insecticides must be environmentally friendly and safe for the ecosystem. Vegetable insecticide was chosen because it is easy to obtain and friendly to the environment. Zodia plants have been widely used by the people, especially the people of Papua as an anti-mosquito. Because of the content of evodiamine, rutaecarpine, and linalool, a-pinene is very effective as a mosquito repellent. Three ways of working plant-based insecticides work, namely: contact poison, gas poison and stomach poison. Research by calculating the average number of mosquitoes - the number of mosquitoes perched on the probandus arm with a concentration of 5%, 10%, 15%, 20%, 25%, 30% proves that the concentration of 25% has a longer protective power of 4 hours with an average of an average of 91%. Other studies say that the concentration of Zodia leaves can last five hours with a concentration of 60% even though it has only 48% protective power. The addition of a fragrant aroma that is fixative can increase protective power. This zodia plant contains linalool (46%) and a-pinene (13.26%). Linalool in zodia leaf essential oils have active ingredients such as evodiamine and rutaceacarpine which have a bitter taste and distinctive aroma.